Legalitas Hukum Kewarisan Anak di Luar Nikah - Munawir (Al-Mizan, 2022)
The order of inheritance to each heir is the will of God whose provisions have been set forth in the provisions of syara', the rules of the game and the completeness of each person with heirs may not be confused with the logic of life. Human law in achieving social change in the era of civilization of human development which is so advanced. Especially in the transfer of inheritance to children whose legality is not recognized in the provisions of the Shari'a to receive inheritance from the heir, in this article the author examines the legality of children out of wedlock. This article uses normative legal research methods (doctrinaire legal studies) or called library research, with data sources namely the Compilation of Islamic Law Article 186 on inheritance and secondary data, namely legal literature on the inheritance of children outside of marriage. The data analysis technique in the research that the author uses is qualitative analysis, namely data analysis by describing the data. The results of the author's research that the provisions of Islamic inheritance for children out of wedlock are not recognized in the syara' law, but this is in line with civil law as stipulated in article 186 concerning inheritance.